Characteristics of general practitioner referrals to podiatrists in Australia, 2000–2016. (April 2021) - Menz, H.B.; Harrison, C.; Bayram, C.
Abstract: Objective: The aim of the study was to describe patterns of referral to podiatrists by general practitioners (GPs) in Australia. Study design: This is a continuous cross-sectional study of Australian general practice activity. Methods: We analysed data from the Bettering the Evaluation and Care of Health program, collected from April 2000 to March 2016 inclusive. Data were summarised using descriptive statistics with 95% confidence intervals around point estimates. Multivariate logistic regression was used to identify GP and patient characteristics independently associated with referral. Results: The data set included 1, 568, 100 encounters, including 5, 912 podiatry referrals. Referrals increased from 7.0 to 39.5 per 1000 population over the evaluation period. In multivariate analyses, female GPs were more likely than male GPs to refer, and GPs aged ≥55 years were less likely to refer. Patients referred to podiatrists were more likely to be aged ≥85 years, be Indigenous, be from an English-speaking background and have previously been seen at the practice. The problem generating the highest number of referrals was diabetes. After the introduction of Medicare funding, referred patients were more likely to be women, be aged >45 years, have a healthcare card, be socio-economically disadvantaged and have previously been seen at the practice. Conclusions: GP referral to podiatrists in Australia increased markedly after the introduction of Medicare funding and appears to be targeted to those with the greatest need. Further research is required to determine whether this policy has improved outcomes and is cost-effective. Highlights: We analysed 5, 912 Australian GP podiatry referrals, April 2000 to March 2016. Female GPs and younger GPs were more likely to refer. Referred patients were more likely to be aged ≥85 years. Referrals to podiatrists increased markedly following the introduction of Medicare funding.